Project based learning: higher education students`perceptions - Alves, Paulo (2020)
The society’s social and technological context is in constant change, which causes the need to innovate and experiment changes in higher education, namely as far as teaching and learning strategies are concerned. In this paper, particular emphasis is given to the assessment of the teaching and learning strategy known as Project Based Learning (PBL). Among the features characterizing this strategy, we highlight the possibility that students have of: learning by doing and by applying their own ideas, getting involved in real-world activities applicable to the world of work, researching questions and issues, discussing ideas, and elaborating and executing projects. According to several authors, who will be cited in the article, the PBL methodology makes students more creative and constructive and helps them develop skills for researching and developing solutions to the problems they might face in their professional life, by learning to solve problems with increasingly higher levels of complexity. Students’ perceptions on the project based learning strategy were obtained from a sample of subjects attending a course in software development in a Portuguese public higher education institution. This course started in the academic year of 2017/2018 and is integrated in a nationwide pilot project, included in the Portuguese Government initiative INCoDe.2030. The main aim of this course consists of training professionals in the field of computing programming who will develop skills to respond to the needs of the real world, as well as fomenting intervention projects within the community. The predominant methodological strategy in all the course units is anchored in Project Based Learning. The main aim of this paper is to assess the Project Based learning strategy, namely by identifying the students’ level of satisfaction and motivation with the strategy used, its strengths and weaknesses, aspects that can be improved, and the skills acquired. The methodology used in this research work is a mixed one, with both qualitative and quantitative characteristics and with procedures associated with experimental research. The main data collection tool used was the survey. The results of this research provide the characterization of the Project Based Learning strategy from students’ perspective, and highlight indicators which enable the assessment of the referred strategy’s strengths and weaknesses as well as the reference to some skills acquired by the students, aiming to the eventual improvement of the strategy and its extension to other courses. Project Based Learning may constitute an approach which is well received by students and enables them to get involved into the paths of innovation and updating, needed to meet the demands of the 21st century.